The Digital Dilemma of Older Adults and Social Participation Mechanisms from the Perspective of Social Exclusion Theory - Kong, Yao (International Journal of Social Sciences and Public Administration, 2026)
In the context of deepening digitalization, older adults face multidimensional social exclusion due to limited access to technology, insufficient institutional adaptation, and cultural barriers. This exclusion is manifested in a chain logic of “inaccessible entry, unattainable processes, and lack of agency in outcomes.” It not only exacerbates the digital divide but also directly restricts opportunities and channels for social participation. Anchored in Social Exclusion Theory and supplemented by Digital Divide and Social Participation Theory, this study systematically analyzes the underlying causes of older adults’ digital dilemmas and their impact on social participation, illustrated through scenario-based cases. On this basis, the study proposes a Social Participation Mechanism composed of technological empowerment, institutional protection mechanism, social support, capacity building, and multi-actor collaborative governance. This mechanism seeks to reverse the logic of “exclusion–restriction–disengagement”and promote sustained, effective, and dignified inclusion of older adults in the digital society. The findings not only enrich the application of Social Exclusion Theory in digital contexts but also provide actionable pathways for digital governance and aging-related social policies.